Removal of trisacryl red using hydrogels composites based on chitosan - Sebti, Houari; Dib, Nihel; Sebba, Fatima Zohra; Bounaceur, Boumediene (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2023)
This study entails the radical copolymerization synthesis of (2-acrylamido-2-methyl-1-propane sulfonic acid) AMPS, utilizing (N,N’methylene bis-acrylamide) MBAm as a cross-linking agent and potassium persulfate (PPS) as an initiator to produce chitosan-based composite hydrogels. The investigation involved the various masses of chitosan (250, 500, and 1000 mg). The characterization of the obtained composites and the dye adsorption process was carried out using FTIR, TGA, SEM, UV-visible, and STEM techniques. Swelling properties in distilled water were examined, revealing that the swelling rates at temperatures of 25°C and 37°C for the hydrogel of poly(AMPS-g-MBAm)/chitosan (1000 mg) exceed those of hydrogels with poly(AMPS-g-MBAm)/chitosan (250 and 500 mg). Furthermore, the sorption capacities of the dye were investigated, demonstrating that the sorption capacities of poly (AMPS-g-MBAm)/chitosan (1000 mg) at different temperatures surpass those of poly(AMPS-g-MBAm)/chitosan (250mg, and 500 mg).